JENIS KONJUNGSI PADA JANJI GADIS TUNGGAL DAN HUBUNGANYA DENGAN PEMBELAJARAN BAHASA INDONESIA - Napitupulu, Otniel Wijaya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2024)
This study was conducted because it is very important to see the use of conjunctions in a text, through the use of the right conjunctions, the writing that will be conveyed is easily understood by the reader. By using the right conjunctions, the text conveyed will be easily understood by the reader. This study aims to analyze the types of conjugations in Andrew Aurelius' short story Promise of a Single Girl and their relationship with Indonesian language learning at Xin Zhong High School, Surabaya. This short story tells of a girl who made a promise to her father before his father died to protect Indonesia and replace his father's profession as a servant of the state. The research method was carried out qualitatively based on content analysis using descriptive techniques. The object of research is the short story Promise of a Single Girl by Andrew Aurelius, a student of SMA Xin Zhong Surabaya. As for the techniques, document techniques and data analysis techniques. Presentation of data as a source of information obtained systematically. The data grouping method used in this research is called the library research method. Library research focuses on collecting library information, reading, recording, and classifying research materials. Based on the analysis carried out, it shows that there are four types of conjunctions, namely conjunctions between words, between clauses, between sentences and conjunctions between paragraphs. As well as its relationship with learning Indonesian at Xin Zhong Senior High School, Surabaya.